Proceedings of the 8th International Conference on Interaction Design and Children 2009
DOI: 10.1145/1551788.1551874
|View full text |Cite
|
Sign up to set email alerts
|

Family communication

Abstract: We interviewed and observed families in their homes to understand how they communicate across generations and across distances. The phone is still the most common way for keeping children in touch with distant relatives. However, many children can't talk on the phone by themselves until 7 or 8 years old. This paper examines the challenges children have with phone conversations, and looks at how families are currently working around these issues. These findings can help inform the design of future family commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(21 citation statements)
references
References 4 publications
0
16
0
5
Order By: Relevance
“…Investigation of which aspects of this communication medium are the most beneficial or problematic for young children is also required. As previous research has shown that young children have difficulties with traditional telephone conversations [2] , it would be beneficial to extend the current protocol to investigate differences in a child's behavior with the availability of their parent via a video link compared to an audio stream and compared to actual presence. Future studies should also include children younger than those included in the present study, and also involve extended relatives rather than parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of which aspects of this communication medium are the most beneficial or problematic for young children is also required. As previous research has shown that young children have difficulties with traditional telephone conversations [2] , it would be beneficial to extend the current protocol to investigate differences in a child's behavior with the availability of their parent via a video link compared to an audio stream and compared to actual presence. Future studies should also include children younger than those included in the present study, and also involve extended relatives rather than parents.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that physical proximity is necessary for attachment seemed obvious (if not tautological) since a sufficient degree of interactivity seemed necessary for a child to form a close relationship with another person, and there was no modality for inter-activity other than physical proximity. The apparent case that physical presence is needed is strengthened by previous research indicating that young children have difficulties with traditional telephone conversations [2]. Now, with video communication, it is feasible for people to have real-time enriched communication without physical proximity.…”
Section: Introductionmentioning
confidence: 99%
“…While parents have been long concerned with the effects of media exposure on young children, research suggests that video chat may encourage more interactive adult-child exchanges than other media-based activities such as playing solo games ( Roseberry et al, 2014 ). Video chatting engages children for longer periods of time, for example, with long-distance family members than traditional phone calls ( Ballagas et al, 2009 ), promoting social relationships with family and friends. Children have access to devices for video chatting at an early age.…”
Section: Introductionmentioning
confidence: 99%
“…Many young children today are geographically separated from their immediate or extended families, and remote communication is an important resource for them (McClure & Barr, 2016). Telephones can be difficult to use for children under 7 years of age (Ballagas, Kaye, Ames, Go, & Raffle, 2009), however, and video chat has been suggested as a viable alternative because it offers opportunities for visual communication (Ballagas et al, 2009;Tarasuik, Galligan, & Kaufman, 2013). Mobile device usage is widespread, even among children under 1 year of age, with many children using a device daily by age 2 (Kabali et al, 2015).…”
mentioning
confidence: 99%